2017
DOI: 10.1039/c7tb00376e
|View full text |Cite
|
Sign up to set email alerts
|

Novel method for the fabrication of ultrathin, free-standing and porous polymer membranes for retinal tissue engineering

Abstract: Retinal degeneration causes permanent visual loss and affects millions of people worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Free-standing porous membranes are strongly required for a wide of practical applications that include biomedical engineering, water treatment, air purification, and catalysis [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Free-standing porous membranes are strongly required for a wide of practical applications that include biomedical engineering, water treatment, air purification, and catalysis [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Y79 cells express both cone-and rod-specific antigens [31][32][33] , and among ARPE-19 cells on the PCL membrane than that of a transwell membrane [16] . The ultrathin membrane is successfully utilized in this research to support ARPE-19 cell seeding, proliferation and formation of monolayer.…”
Section: Discussionmentioning
confidence: 99%
“…The bioprinting procedure was based on the drop-by-drop pattern to achieve a final seeding density of 2,786 ± 492 cells/cm 2 on an ultrathin membrane. The ultrathin membrane was fabricated according to our published protocol [16] . Then, the cells on the ultrathin membrane were further cultured for two weeks.…”
Section: Arpe-19 Cell Bioprintingmentioning
confidence: 99%
“…Although TIPS allows the formation of a wellinterconnected polymer network, it does not allow for the adjustment of the pore size. It has been demonstrated that the ultrathin porous membrane, fabricated by separation phase, could act as a potential prosthetic BrM for RPE transplantation [99] . 3D printing Although conventional fabrication techniques have been widely used for scaffold preparation, they still lack fine control of structural aspects, such as the porosity, and scaffold dimensions and size.…”
Section: Scaffold Fabricationmentioning
confidence: 99%